Tropical south east Atlantic warm events and associated rainfall anomalies over southern Africa - Reason, Chris J. C.; Smart, Sandi (Frontiers in Environmental Science, 2015)
Moisture flux and rainfall anomalies over southern Africa that have occurred during strong warm SST events off the coast of Angola since 1950 are considered. These events typically occur during February-April (FMA), the main rainy season for Angola / northern Namibia. Eleven of these events have occurred in this sixty year period and each experiences increased rainfall somewhere in coastal Angola, and in ten cases, somewhere in northern Namibia. Attention is focussed on the five events with the largest and most widespread positive rainfall anomalies over Africa south of 10oS; namely, 1963, 1986, 2001, 2006, 2011. All of these five events experienced increased moisture flux from the western tropical Indian Ocean, warm SST anomalies also in the south west Indian Ocean, and most also showed increased westerly moisture flux from the tropical south east Atlantic. The events also showed strong weakening of the mid-level anticyclonic conditions that occur over southern Africa during summer. This factor together with the distribution of anomalous uplift through the middle/upper troposphere appeared to match the areas of increased rainfall better than the areas of low level moisture convergence. Reported experiments with an atmospheric GCM forced with idealisations of the observed SST anomalies show rainfall anomalies consistent with the observed patterns.